Analisis GC-MS dari Senyawa Bioaktif Ekstrak Etanol Daun Tanaman Sirsak (Annona muricata L.) sebagai Obat Tradisional - Saputra, I Putu Bayu Agus; Sukanty, Ni Made Wiasty (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Soursop leaves (Annona muricata L.), have long been recognized in various parts of the world, especially in tropical regions, as a plant with various health benefits and traditional uses. The rich history of its use has been intertwined in various cultures, where the leaves are used not only as a food ingredient, but also as a herbal medicine. The phytochemical content in soursop leaves, such as acetogenin, alkaloids, and flavonoids has been the subject of intensive research in the last decade, highlighting their potential in treating a variety of health conditions, from inflammation to anti-cancer potential. The chemical structure and biological activity of these compounds have attracted the attention of researchers, especially in the search for alternative therapies for difficult-to-treat diseases. Soursop leaf extract has antioxidant, antimicrobial, antiparasitic, and antitumor properties that offer new insights into its therapeutic potential. This research method uses the maceration method, where soursop leaves will be extracted using ethanol solvent and then the compounds contained in the extract will be analyzed using Gas-Mass Spectrometry (GC-MS). The results of GC-MS analysis show that soursop leaves contain the compounds 2,3-Dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one, Trans-Caryophyllene, Hexadecanoic acid (CAS) Palmitic acid, 2-Hexadecen- 1-ol, 3,7,11,15-tetramethyl (Phytol), 9,12-Octadecadienoic acid (Z,Z) - (CAS) Linoleic acid, 9,12,15-Octadecadienoic acid methyl ester, Octadecanoic acid (CAS ) Stearic acid. The results of the analysis of compounds in soursop leaves can be a reference for further research to develop the potential of soursop fruit which leads to traditional medicine.